Research and Technology Commercialization - Markman, Gideon D.; Siegel, Donald S.; Wright, Mike (Journal of Management Studies, 2008)
abstractThis paper introduces the special themed section on organizational interactions involving universities and firms that result in the commercialization of research and technology. Our objective is to shed light on some of the most vexing, yet under‐researched predicaments research institutions encounter, despite their best efforts to advance commercialization. First, we synthesize and extend recent studies, including the papers in the special themed section. Next, we develop a taxonomy of modes of commercialization. Specifically, we consider internal approaches, quasi‐internal approaches (e.g. incubators), university research parks, regional clusters, academic spin‐offs and start‐ups, licensing, contract research and consultancy, corporate venture capital, and open science and innovation. We also identify areas for further research at the individual (e.g. heterogeneity of entrepreneurial teams and experience; incentives), organizational and intra‐university (e.g. corporate governance; nature of growth strategies; relationships with trading partners; boundary spanning activities) and technology levels (e.g. institutional context; reconfiguration of technology; valuation of technology).